Implementasi Program Literasi Sebagai Upaya Menumbuhkan Minat Baca Peserta Didik Kejar Paket A di SKB Kota Malang - Widodo, Rika Angelina; Yulianingsih, Wiwin (J+PLUS UNESA, 2023)
The non-formal educational institution that has recently re-promoted the implementation of the literacy program is the SKB Malang City. However, students pursuing package A have low interest in reading. With this in mind, the researcher wants to examine the implementation of the literacy program as an effort to foster interest in reading for students pursuing package A at SKB Malang City. This study aims to determine the implementation of the literacy program as an effort to foster interest in reading in students pursuing package A, to examine the supporting factors and inhibiting factors in the implementation of the literacy program as an effort to foster interest in reading in students pursuing package A. This research uses a qualitative approach. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the implementation of the literacy program is supported by a). Communication is done internally; b). Resources that support this activity include the involvement of all members of the learning activity studio, the existence of special funds from the BOP, and allocating special time for literacy activities; c). Disposition; d). The bureaucratic structure forms the composition of the literacy task force committee.